Multiple critical pole maximally flat RC active filter with sharp cutoff - Thajchayapong, P.; Kimpan, C.; Rungsunseri, Y. (My University, 1986)
A maximally flat RC active filter with sharp cutoff can be achieved by including single or multiple pairs of coincident transmission zeros but at the expense of high Q-factor of the critical pole pair. A novel design technique is proposed here to reduce the Q-factor of such filters by increasing the multiplicity of the critical pole pairs. Hence a new class of sharp cutoff maximally flat RC active filters with low sensitivity is obtained. © 1986, The Institution of Electrical Engineers. All rights reserved.
Keywords: Active networks; Circuit theory and design; Design; Filters and filtering